The impact of blood glucose and HbA1c goals on glycaemic control in children and adolescents with Type 1 diabetes. Issue 3 (20th February 2013) - Boot, M.; Volkening, L. K.; Butler, D. A.; Laffel, L. M. B.
Abstract Aims To evaluate parents' goals and parents' perceptions of physicians' goals for blood glucose and HbA1c in children and adolescents with Type 1 diabetes. Methods In a cross‐sectional observational assessment, parents (80% mothers) of 153 children/adolescents (56% female), aged 12.9 ± 2.3 years (range 8–16 years) with Type 1 diabetes for 6.3 ± 3.5 years, completed surveys regarding their goals and their perceptions of physicians' goals for their child's blood glucose and HbA1c levels. Results Children/adolescents had a mean HbA1c of 69 ± 16 mmol/mol (8.4 ± 1.4%) and checked blood glucose levels 3.8 ± 1.2 times/day; 23% received pump therapy. Almost half of parents reported a blood glucose goal of 130 (80–180) mg/dl [7.2 (4.4–10) mmol/l]; 75% of parents reported a HbA1c goal of 42–64 mmol/mol (6–8%). HbA1c was significantly lower when parents reported HbA1c goals ≤ 64 mmol/mol (≤ 8%) vs. > 64 mmol/mol (> 8%) [67 ± 14 mmol/mol (8.3 ± 1.2%) vs. 76 ± 20 mmol/mol (9.1 ± 1.8%), respectively, P = 0.02]. Parents' blood glucose and HbA1c goals were tightly linked with parents' perceptions of physicians' blood glucose and HbA1c goals (69% concordant, P < 0.0001; 88% concordant, P < 0.0001, respectively). Conclusions There was a significant association between lower parent HbA1c goals and lower child/adolescent HbA1c. Further, parents appear to set glycaemic goals based upon their perceptions of physician goals. Future studies should assess the relationship between parents' perceptions of health‐care providers' goals and health‐care providers' actual goals and the impact of unified family/provider goal‐setting on glycaemic control.